rTSA With Humeral Head Autograft Glenoid Reconstruction - Soheil Sabzevari MD; Ryan Eads MD; Shaquille Charles MSc; Rajiv P. Reddy BSc; Albert Lin MD (SAGE Publishing, 2023)
Background: Untreated chronic massive rotator cuff tears and primary osteoarthritis can lead to conditions of significant retroversion, posterior bone loss, and humeral head subluxation. Indications: Reverse total shoulder arthroplasty with humeral head autograft glenoid reconstruction may be indicated in patients with advanced glenohumeral osteoarthritis and/or severe glenoid retroversion/bone loss due to rotator cuff arthropathy, trauma, primary, or inflammatory osteoarthritis. Technique: Besides routine radiography and preoperative computed tomography (CT) scans, 3-dimensional (3D) planning software is often performed as a routine part of preoperative planning. A 3D printed model of the glenoid can also be helpful in cases of significant bone deformity. Patients are placed in a 45° modified beach chair position. Using a standard deltopectoral approach, the glenoid is exposed. An anatomic humeral head resection is made. The contour of the articular margin of the humeral head should match the glenoid bone deficiency anatomically as it has been chronically resting within the glenoid defect. Three dimensional preoperative planning and the 3D printed model are used to make an asymmetric humeral head autograft which should match the deficiency perfectly. The articular cartilage is removed with a burr. The graft and baseplate are coupled together (metaphyseal bone facing the baseplate and prepared articular side of the graft facing native bone) and measurements are performed with the preoperative planning software to fashion a graft with the appropriate dimension and with the desired amount of lateralization. The bone graft is then compressed with the baseplate to the native glenoid and fixed with screws. Results: In select patients with careful preoperative planning, excellent outcomes can be achieved with careful gradual resumption of range of motion and strength with physical therapy. Sequential radiographic imaging is performed up to 6 months and beyond to confirm solid union of graft to native glenoid bone and incorporation into the baseplate. Discussion/Conclusion: Reverse total shoulder arthroplasty (rTSA) with humeral head autograft glenoid reconstruction is an excellent option to address severe glenoid bone loss and restore the native joint line for both primary osteoarthritis and rotator cuff arthropathy. Using 3D CT scans, 3D preoperative planning software and 3D printing of the glenoid can help achieve a good outcome. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.